Microparticles for diagnosis of graft-versus-host disease after allogeneic stem transplantation - Rank, Andreas; Nieuwland, Rienk; Toth, Bettina; Pihusch, Verena; Delker, Ruth; Hiller, Erhard; Kolb, Hans-Jochem; Pihusch, Rudolf (Transplantation, 2011)
Background. - The differentiation between acute graft-versus-host disease (aGvHD) and infection is still a clinical challenge in patients after allogeneic hematopoietic stem-cell transplantation (HSCT). Definitive diagnosis is based on histologic findings, but a simple blood test for differentiation is missing. - Methods. - In a prospective study, we measured the plasma levels of erythrocyte-derived microparticles (EryMP) in 19 recipients during HSCT. Microparticles were isolated by differential centrifugation, double stained for glycophorin A (CD235) and annexin V, and analyzed by flow cytometry. - Results. - Eight patients developed aGvHD (42%), 15 patients developed infectious complications (79%), and two patients developed microangiopathic hemolytic anemia (11%). The levels of EryMP, as measured before conditioning therapy (535×106/L in median), were not affected by total body irradiation, high-dose chemotherapy, or in vivo T-cell depletion. EryMP levels were unaffected in uncomplicated patients during aplasia (522×106/L in median; P=0.394) or after engraftment (480×106/L in median; P=0.594) and in patients with infectious complications or sepsis (586×106/L in median; P=0.606). In contrast, in patients who developed aGvHD after HSCT, a 1.7-fold increase in the plasma levels of EryMP was observed (880×106/L in median; P<0.001 compared with the time before therapy and P=0.015 compared with patients with infections or sepsis). - Conclusion. - Increased plasma levels of EryMP are present in patients who develop aGvHD but not in patients who develop infection or sepsis after HSCT. Therefore, EryMP are a potential, novel, blood marker that may be helpful in the diagnosis of this common complication after HSCT.